A Conceptual Model of Mobile Augmented Reality for Hearing Impaired Museum Visitors’ Engagement - Baker, Esraa Jaffar; Abu Bakar, Juliana Aida; Zulkifli, Abdul Nasir (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Many studies have begun to consider how to ensure a pleasant experience during visits to cultural heritage sites and museums. Although, when considering the populace of the visitors to these sites, the hearing impaired (HI) visitors which made up of a smaller percentage, have not been in the literature limelight as much as the normal hearing visitors. Thus, the hearing impaired tends to endure certain unpalatable experiences leading to dissatisfaction of their visits. Literature has shown that Mobile Augmented Reality (MAR) can improve the experiences of visitors to the museum in terms of engagement, enjoyment and learning. This is evident in a number of articles tailored towards normal hearing visitors. However, a recent study has taken into consideration the hearing impaired visitors by identifying the engagement elements of MAR for the HI museum visitors. The identified elements include; aesthetics, interaction, interest, usability, satisfaction, motivation, curiosity, enjoyment, perceived control, self-efficacy, and focused attention. This article thus takes a step further by introducing the MAR for the HI museum visitors’ engagement (MARHIME) conceptual model. These elements are derived from a review of literature which has been done comprehensively and are validated by a panel of experts. Altogether eleven elements went through the expert review process and only six elements were validated to be used for the construction of the MARHIME model. This article also further grounds the justification of these selected six elements in relation to engagement. Future work will include the development of the MARHIME prototype which will be used to validate the model among the hearing impaired visitors at a museum.